2020
DOI: 10.1515/jpem-2019-0134
|View full text |Cite
|
Sign up to set email alerts
|

Gender-based differences in the clustering of metabolic syndrome factors in children and adolescents

Abstract: BackgroundWe depicted gender-differences in metabolic syndrome (MS) clustering before and after puberty in pediatrics, in order to develop gender specific preventive strategies for childhood obesity.MethodsWe considered 1079 children and adolescents (529 females and 550 males; mean age 11.5 ± 2.8 year). According to body mass index (BMI) percentiles the subjects were classified as normal weight BMI <75th, overweight BMI 75–95th and with obesity BMI >95th. MS was diagnosed when three of the following crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…Weight, height, and blood pressure are recorded as previously described [25]. BMI was calculated as body weight (kilograms) divided by height (meters squared).…”
Section: Clinical Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Weight, height, and blood pressure are recorded as previously described [25]. BMI was calculated as body weight (kilograms) divided by height (meters squared).…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…Waist circumference was measured as previously described [25]. WHtR, ABSI, TMI, VAI, and Con-I were calculated as follows:…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…These findings parallel the majority of previous research on sex differences in MetS components among civilian youth. 2,4,5 There are several potential explanations for these observed sex differences. Lifestyle factors may partially explain these differences, as a previous study in treatment-seeking adolescents with severe obesity found that boys reported more screen time, higher intake of sugar-sweetened beverages and soda, and lower intake of vegetables compared to girls.…”
Section: Discussionmentioning
confidence: 99%
“…2 Similarly, a cross-sectional study of treatment-seeking adolescents with severe obesity found that, compared to girls, boys had significantly higher triglycerides and systolic blood pressure, as well as lower HDL-C. 4 In another sample of children and adolescents across all weight strata, boys had higher waist circumference, fasting glucose, and systolic blood pressure. 5 However, the data are not entirely consistent. For example, one study found that girls were more likely to have multiple metabolic This article is protected by copyright.…”
Section: Sex Differences In Metabolic Syndrome Components In Adolescent Military Dependents At High-risk For Adult Obesitymentioning
confidence: 91%
“…Abdominal adiposity and visceral fat were positively associated with elevated blood pressure and dyslipidaemia in children, independent of BMI [15,16]. This could be sex specific; indeed, in a large sample of children and adolescents, boys showed a higher WC, WHtR, fasting glucose level, and systolic blood pressure, independent of BMI [17]. In addition, in the last few decades, a higher increase in waist circumference compared to BMI was observed, suggesting that abdominal adiposity has proportionally increased more than overall body fatness [18].…”
Section: Introductionmentioning
confidence: 91%